Criminal offense of trafficking in human beings: International documents, contemporary solutions in national legislations and Criminal Code of Federal Republic of Yugoslavia - Nikolić-Ristanović Vesna Ž.; Ćopić Sanja M. (Temida, 2002)
Due to its high social danger and far-reaching consequences, trafficking in human beings, as a form of transnational crime, needs an all-inclusive international approach in countries of origin, transit and destination. That means the use of effective measures concerning prevention, punishment of perpetrators and protection of victims. In connection with that, intensive efforts of the international community in stamping out this phenomenon marked the end of 20™ century. They are incarnated in a numerous of international documents and other activities, which particular emphasize the need of criminalization of trafficking in human beings in national legislation. In the paper, authors are analyzing international documents that are both directly or indirectly dealing with this topic, as well as criminal law provisions of a number of countries (USA, Western Europe, Central and Eastern Europe, Southern Europe). The aim of such an approach is to perceive our legislation though the prism of the contemporary tendencies, as well as to point out certain shortages and the importance of harmonizing our legislature with the international standards and demands of the international community. The first step toward that should be inclusion of trafficking in human beings as a separate criminal offence in the Criminal Code of Federal Republic of Yugoslavia. Victimology Society of Serbia drafted such criminal law provision, which is presented in this paper.